Patch Testing In Soldiers : An Evaluation - Walia N. S; Jaiswal A. K (Wolters Kluwer Medknow Publications, 2004)
Our study concerns contact sensitization in soldiers, the frequency of which is poorly documented. During a six-year period, 128 patients of age range 17-50 years were patch tested with the Indian standard battery of 30 allergens. We obtained a reaction in 23 (18%) of our patients. Nickel sulfate, fragrance mix, wool alcohol and parthenium induced most of the positive responses. In addition, an irritant reaction was seen in 16 (12.5%) of our patients. Patients of atopic dermatitis and hand/foot dermatoses evoked a high sensitivity response. Adverse effects were seen in 15 patients.